LEARNER AUTONOMY IN ACCESSING WEB-BASED EFL LEARNING; CASE AT ENGLISH DEPARTMENT OF MUHAMMADIYAH UNIVERSITY OF PONOROGO - Cahya Ratrina; Ana Maghfiroh; Niken Reti Indriastuti; Siti Asiyah (PROJECT (Professional Journal of English Education), 2022)
Web-based learning gives student more opportunities with resources than learning in a traditional class. Therefore, this research is also to find out how learners can be independent in accessing web-based resources. This research was qualitative descriptive research with the research subjects were sixth semester students of English Education Department, University of Muhammadiyah Ponorogo. The number of participants was 12 students. Data collection techniques in this study were conducted through interview techniques and distributing questionnaires through google form. The data analysis technique used three analytical techniques consisting of data reduction, data presentation, and drawing conclusions. results of this study showed that lecturers were directly involved in student learning, whether through online or face-to-face instruction, that was crucial for aiding comprehension of the lecture material. Tasks that must be completed within a period of time through web-learning will help students increase their learning independence. Web-based learning increased students' independence by enabling them to take advantage of flexible study time. Based on the results of the study, it showed that face to face or offline learning is more effective because the lecturers would gave the direct guidance or experience. Besides that, students have more opportunities and choices in their language learning through web-based learning.. Web-based multimedia assisted teaching provided students with more chances and choices in their language learning. Keywords:  Autonomous Learning, Web-based Learning, Language, Online